Market information: No more spilt milk - Karamagi, Helene; Nalumansi, Lillian (Technical Centre for Agricultural and Rural Cooperation, 2009)
A group of dairy farmers in rural Uganda now use mobile phones to deal directly with buyers, negotiate prices and organize delivery. Improved access to market information has reformed the way the farmers do business and has led to increased profits.